Wave concept of motion in mathematical models of the dynamics of two-dimensional media studying - Andrukhiv Andrij; Sokil Bohdan; Sokil Mariia (Lviv Politechnic Publishing House, 2019)
The methodology of the studying of dynamic processes in two-dimensional systems by mathematical models containing nonlinear equation of Klein-Gordon was developed. The methodology contains such underlying: the concept of the motion wave theory; the single - frequency fluctuations principle in nonlinear systems; the asymptotic methods of nonlinear mechanics. The aggregate content allowed describing the dynamic process for the undisturbed (linear) analogue of the mathematical model of movement. The value determining the impact of nonlinear forces on the basic parameters of the waves for the disturbed analogue is defined.
Keywords: dispersion ratio, amplitude, frequency, wave number, mathematical model, nonlinear oscillations, asymptotic solution